Conflict Avoidance by Descent Behind the Intruder - Magister, Tone (Promet - Traffic&Transportation, 2004)
The paramount priorities for safe implementation of a singlepilot manned cockpit concept and the futuristic concept of asingle pilot acting as a supervisor for a fully automated aircraftflying on incessantly self-optimised trajectories are eliminationsof the risk of mid-air collisions and of conflicts resulting fromthe lack of safe airborne separations. Avoidance procedureswith initiation of descent behind the intruder for conflict resolutionbetween a pair of aircraft where one of them is in the vicinityof the top of its descent represents merely one little piece ofthis giant puzzle.